Does social capital affect the incidence of functional disability in older Japanese? A prospective population-based cohort study. Issue 1 (3rd July 2012) - Aida, Jun; Kondo, Katsunori; Kawachi, Ichiro; Subramanian, S V; Ichida, Yukinobu; Hirai, Hiroshi; Kondo, Naoki; Osaka, Ken; Sheiham, Aubrey; Tsakos, Georgios; Watt, Richard G
Abstract : Background: Recent increases in numbers of older people have been accompanied by increases in those with functional disability. No study has examined the association between community social capital and the onset of functional disability. Methods: The association between community social capital and the onset of functional disability was examined using data from the Aichi Gerontological Evaluation Study, a prospective cohort established in 2003 in Japan. Perceptions of community social capital (indicators of social cohesion such as trust of others and extent of social participation) in 6953 men and 7636 women aged 65 years or older were surveyed. Multilevel survival analysis using the discrete-time hazard model was applied. Results: During 4-year follow-up, onset of functional disability occurred in 759 men and 1146 women. Women living in communities with higher mistrust had 1.68 (95% CI 1.14 to 2.49) times higher OR of onset of disability, even after adjusting for covariates. Mediators did not substantially change this association. Lack of social participation seemed to affect the health of women, though the effect was marginal (OR for covariates adjusted model =1.12 (95% CI 0.96 to 1.31)). There were no significant ORs among men. Conclusions: Lower community social capital was associated with higher incidence of onset of functional disability among older women but not among men. Community-based interventions to promote social capital may be useful for preventing functional disability of older Japanese women.